The Procedure for Maintaining Accounting Records in Trade Enterprises Based on International Standards: Prosedur Pemeliharaan Catatan Akuntansi di Perusahaan Perdagangan Berdasarkan Standar Internasional - Uzakov Utkir Abdusattarovich (Academia Open, 2025)
General Background: Accounting plays a crucial role in business operations by ensuring accurate financial reporting and transparency. The adoption of International Financial Reporting Standards (IFRS) has become essential for global trade enterprises to maintain consistency, comparability, and reliability in financial statements. Specific Background: Trade businesses face challenges in financial reporting, including compliance with international regulations, efficient data management, and technological adaptation. IFRS provides a standardized framework to enhance financial reporting quality, improve investment prospects, and support decision-making. Knowledge Gap: Despite the widespread adoption of IFRS, gaps remain in understanding the practical implementation of international standards in trade enterprises, particularly regarding accounting policies, automation, and personnel training. Aims: This study analyzes the role of IFRS in trade business accounting, examines key elements such as financial statement preparation, auditing, and technology integration, and identifies challenges and solutions in compliance with global standards. Results: Findings indicate that IFRS adoption enhances financial transparency, improves internal financial discipline, and strengthens businesses' competitiveness in international markets. The integration of modern accounting technologies and training programs significantly improves compliance efficiency. Novelty: This study provides a structured approach to implementing IFRS in trade businesses, highlighting the synergy between regulatory compliance, technological advancement, and personnel expertise. Implications: The adoption of IFRS fosters financial stability, attracts investment, and supports trade enterprises in global market expansion. Policymakers and business leaders should prioritize regulatory adherence, automation, and workforce development to optimize financial reporting processes. Highlights: Importance of IFRS in Business Accounting Technology & Tools for Accurate Financial Reporting Enhancing Global Competitiveness Through Standardized Accounting Keywords: financial reports, International Financial Reporting Standards (IFRS), Joint-stock companies, revenue and expenses.